METODE PEMBELAJARAN IMPROVE TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA - Zulfa Razi; Maryanti Maryanti; Mirunnisa Mirunnisa (LPPM Universitas Bina Bangsa, 2023)
The purpose of this research is to determine whether using the IMPROVE learning approach can improve students' ability to think critically mathematically. This experimental research used a pretest-posttest control group design. This research involved all students in class XI MIPA SMA Negeri 1 Peukan Baro. Two classes, class XI MIPA 1 and class XI MIPA 2, were selected as experimental and control samples. This study uses questions to test students' mathematical critical thinking skills. After the prerequisites for testing were met, the data were analyzed using an independent t-test at a significant level of 0.05. According to the results of data analysis, the value of tcount = 3.839, and the value of Sig. 2-tailed = 0.00043, and the Sig. 1-tailed = 0.000215, because the Sig. 1-tailed = 0.000215 < α = 0.05, which indicates that H0 is rejected and Ha is accepted